Analisis Strategi Indonesia dalam Isu Hak Asasi Manusia (HAM) dalam Hubungan Indonesia–Australia - M. Faiz Intisar Lukvi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Indonesia–Australia relationship is a complex and dynamic bilateral relationship in which human rights (HR) issues frequently become points of diplomatic tension. This article analyzes strategies that Indonesia can employ to gain greater advantage in human rights issues at the bilateral level with Australia. Through a qualitative approach based on literature review and foreign policy analysis, this study identifies three main strategies: (1) normative diplomacy and narrative balancing, (2) strengthening practical Indonesia–Australia cooperation on human rights, and (3) strengthening domestic capacity as a bargaining instrument. The analysis reveals that these three strategies can synergistically enhance Indonesia's international credibility, strengthen its bargaining position in bilateral dialogue, and prevent human rights issues from being used as tools of political pressure by external parties. The implications of this study underscore the importance of a holistic approach that integrates internal reform with external diplomatic strategy to position Indonesia as an equal, competent, and trusted partner for Australia on human rights matters.